The Applications and Distinctions of Three Different Material Collection Plates in Wet Electrostatic Precipitator - Jin-Yuan Syu; Shang-Yan Huang; Yu-Chih Cheng; Shao-Hao Lu; Chih-Te Wang; Yuan-Yi Kao; Wen-Yinn Lin (Aerosol and Air Quality Research)
Abstract Particle back-corona slows the efficiency of the dry-electrostatic precipitator (dry-ESP), especially during the removal of high resistivity particles. In this study, a new type of wet-electrostatic precipitator (wet-ESP) was designed and built using stainless steel (SS), conductive glass (CG), and original glass (OG) for its collection plates. The objectives of this research included the efficiency characteristics of both the dry-ESP and the wet-ESP, how the materials used in the dust collectors affect the ESP performance including SS, CG, and OG, and the effects on the electric resistivity of the particle of its performance, and the ozone generation rates of the wet-ESP. The experiment results indicated that the wet-ESP could improve the dust-cake phenomenon caused by high electrical resistivity particles that often occurred on dry-ESP in order to prolong its efficiency. Furthermore, the results indicated that during the most penetrating particle size (MPPS) penetration of SSESP and CGESP were both below 6% while OGESP was over 40% under the dry condition. When OGESP was placed and operated under the wet condition, its particle penetration dropped to below 20% under the MPPS. The results confirmed that compared to the dry-ESP, wet-ESP performed at a higher and better efficiency. In addition, as ozone concentration acts on the corona current under the same voltage, the result found that the ozone concentration of OGESP was lower than both CGESP and SSESP under the wet setting.